2015
DOI: 10.1016/j.ijms.2014.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Reprint of “Mass-selected supported cluster catalysts: Size effects on CO oxidation activity, electronic structure, and thermal stability of Pd /alumina (n≤ 30) model catalysts”

Abstract: a b s t r a c tAn intense, mass-selected cluster source for preparation of model supported clusters is described, and results are presented for cluster size effects on CO oxidation activity for Pd n clusters supported on alumina films grown on Re(0001) or Ta(110) single crystals. The electronic structure of the samples was probed by X-ray and UV photoelectron spectroscopy, and low energy ion scattering was used to probe binding morphology. The Pd n activity was monitored via both steady state and temperature-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 159 publications
0
20
0
Order By: Relevance
“…In a number of previous studies of cluster size effects on oxidation catalytic activity, 61,62,71,91 we have found sizedependent anticorrelations between core and valence level BEs of the metal clusters, and activity as oxidation catalysts under conditions ranging from UHV to aqueous phase electrochemistry. As shown in Figure 7, the situation here is different.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In a number of previous studies of cluster size effects on oxidation catalytic activity, 61,62,71,91 we have found sizedependent anticorrelations between core and valence level BEs of the metal clusters, and activity as oxidation catalysts under conditions ranging from UHV to aqueous phase electrochemistry. As shown in Figure 7, the situation here is different.…”
Section: Discussionmentioning
confidence: 64%
“…Temperature-dependent ISS shows that these sites are predominantly on top of the clusters, in both cases. 62,64 It is interesting, therefore, that there is an anticorrelation between activity and this high temperature The Journal of Physical Chemistry C Article feature measured for residual CO desorbing during TPR. The anticorrelation presumably stems from competition between CO desorption and CO oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After cleaning the ITO, size-selected Pt n + was deposited using a mass-selecting beamline described elsewhere, 35 with deposition kinetic energy of 1 eV/atom, and the cluster spot was defined by a 2 mm diameter mask located just in front of the substrate. Pt n + neutralized on contact with the conductive ITO, and the neutralization current was monitored continuously to allow deposition to be stopped when the desired coverage was reached.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were conducted with an instrument consisting of a mass-selected metal cluster ion deposition beamline 26 that terminates in an ultrahigh vacuum (∼1.5 × 10 −10 Torr) analysis chamber that allows in situ sample preparation and characterization, as discussed previously, along with several of the experimental protocols used here. 12,27,28 The Pt n /alumina model catalysts were prepared on a 7 × 7 mm Ta(110) single crystal mounted using Ta heating wires to a liquid nitrogen reservoir at the end of a manipulator. The sample temperature was controlled between 110 and >2100 K by the combination of resistive and electron-bombardment heating and liquid nitrogen cooling.…”
Section: Methodsmentioning
confidence: 99%